2013
DOI: 10.1002/ibd.23034
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of CXCL10 in Inflammatory Bowel Disease

Abstract: We explored the gene expression in colonic biopsies of active and inactive inflammatory bowel disease (IBD), in an extensive material of ulcerative colitis (UC) and Crohn`s disease (CD). The chemokine CXCL10 and its receptor CXCR3 were among the upregulated genes.This study examines the expression of CXCL10 and the mechanisms for its release in patients with UC or CD, and in intestinal epithelial cell (IEC) lines. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 31 publications
2
32
1
2
Order By: Relevance
“…Therefore, enterocytes are active producers of CXCL10 in the duodenum of CD patients during the inflammatory process, and this production of CXCL10 is triggered by gluten intake. Although this study provides the first demonstration of the production of CXCL10 by enterocytes in the small intestine, similar results have been described in the colon [32], [33], and recently, the upregulation of CXCL10 was observed in colonic enterocytes in inflammatory bowel diseases [9]. Altogether, these findings indicate that enterocytes actively produce CXCL10 in a chronic inflammatory setting.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, enterocytes are active producers of CXCL10 in the duodenum of CD patients during the inflammatory process, and this production of CXCL10 is triggered by gluten intake. Although this study provides the first demonstration of the production of CXCL10 by enterocytes in the small intestine, similar results have been described in the colon [32], [33], and recently, the upregulation of CXCL10 was observed in colonic enterocytes in inflammatory bowel diseases [9]. Altogether, these findings indicate that enterocytes actively produce CXCL10 in a chronic inflammatory setting.…”
Section: Discussionsupporting
confidence: 89%
“…2124 IL-8 is a chemo attractant that induces neutrophil chemo taxis and phagocytosis, and IP-10 is a chemokine that attracts inflammatory cells. 2529 MMP-3 degrades extracellular matrix under inflammatory conditions, 14 and S100-A8 is a subunit of cal protect in, a biomarker for fecal inflammation, that is used to monitor disease activity in inflammatory bowel disease. 16, 30, 31 …”
Section: Methodsmentioning
confidence: 99%
“…Elevated amounts of LCN2 have been detected in mice fed a high-fat, high-salt diet and in colitis models (5). Recent studies of patients with IBD showed that LCN2 was among the 10 most upregulated genes in both active ulcerative colitis and active Crohn's disease compared with healthy controls (192). LCN2 protein was found in both epithelial cells and infiltrating neutrophils, whereas mRNA synthesis was detected only in epithelial cells.…”
Section: Biomarkers Of Intestinal Epithelial Permeability and Integrimentioning
confidence: 99%